Prediktor Internal dan Eksternal Suicidal Ideation Remaja - Fitria, Ika; Yusainy, Cleoputri; Rahma, Ulifa; Rachmayani, Dita (Mediapsi, 2025)
The desire to survive is a basic human instinct, but the transitions and role changes in adolescence could paradoxically trigger suicidal ideation. In this correlational study (N = 202, 86.14% female; age range 12-20 years, Mage = 19, SDage = 2.77), we examined the extent to which adolescents' suicidal ideation (Scale for Suicide Ideation: SSI) could be predicted by levels of their perceived social support (Multidimensional Scale of Perceived Social Support: MSPSS), self-efficacy (General Self-Efficacy Scale), and depression (Beck Depression Inventory: BDI-II). We found that these three variables simultaneously predicted suicidal ideation by 52%. Self-efficacy perceived social support, and depression also partially predicted suicidal ideation (11.2%, 29.2%, and 47.12%). Mental health promotion, prevention programs, and coping strategies focusing on suicidal ideation would benefit from an early identification of how these three variables may interact with each other in adolescents.